1991
DOI: 10.1302/0301-620x.73b1.1991745
|View full text |Cite
|
Sign up to set email alerts
|

Tarsal tunnel syndrome. Causes and results of operative treatment

Abstract: From 1975 to 1988, operative treatment was performed on 50 feet in 45 patients with tarsal tunnel syndrome. The causes of this syndrome were correlated with operative findings and included ganglia in 18, and a bony prominence from talocalcaneal coalition in 15. Five feet had sustained an injury, tumours were Y. Takakura,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
85
0
7

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 144 publications
(93 citation statements)
references
References 2 publications
1
85
0
7
Order By: Relevance
“…According to the rating system of Takakura et al [27], there were excellent results in three feet, good results in six, fair results in two and poor results in two. Of six cases, with a mean pre-operative duration of symptoms of 52.3 months, two were being treated with a diagnosis of a prolapsed intervertebral disc, three tendonitis and one plantar fasciitis.…”
Section: Methodsmentioning
confidence: 95%
See 4 more Smart Citations
“…According to the rating system of Takakura et al [27], there were excellent results in three feet, good results in six, fair results in two and poor results in two. Of six cases, with a mean pre-operative duration of symptoms of 52.3 months, two were being treated with a diagnosis of a prolapsed intervertebral disc, three tendonitis and one plantar fasciitis.…”
Section: Methodsmentioning
confidence: 95%
“…The incidence of a satisfactory outcome after surgical treatment varies between 44% and 95% [9,15,20,27]. The importance of seeking a precise diagnosis has been stressed, and it has been suggested that conservative measures should be continued for some time in patients without a space-occupying lesion [20,28].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations